A note on discrete-time dynamical systems under periodic perturbation - Huimin Li; Xiaosong Yang (Discrete Dynamics in Nature and Society)
We present some results on the existence and the minimum period of periodic orbits for discrete-time dynamical systems under periodic perturbation. Some examples are presented to illustrate these results.